Viral delivery of a peptide-based immunomodulator enhances T cell priming during vaccination - Phares, Timothy W.; Huang, Jing; Kotraiah, Vinayaka; Hauser, Mary J.; Domi, Arban; Oruganti, Sreenivasa; Browne, Cecille D.; Buontempo, Peter; Mansour, Marc; Pannucci, James; Tsuji, Moriya; Gutierrez, Gabriel M. (Frontiers in Pharmacology, 2022)
Modern, subunit-based vaccines have so far failed to induce significant T cell responses, contributing to ineffective vaccination against many pathogens. Importantly, while today’s adjuvants are designed to trigger innate and non-specific immune responses, they fail to directly stimulate the adaptive immune compartment. Programmed cell death 1 (PD-1) partly regulates naïve-to-antigen-specific effector T cell transition and differentiation by suppressing the magnitude of activation. Indeed, we previously reported on a microbial-derived, peptide-based PD-1 checkpoint inhibitor, LD01, which showed potent T cell-stimulating activity when combined with a vaccine. Here we sought to improve the potency of LD01 by designing and testing new LD01 derivatives. Accordingly, we found that a modified version of an 18-amino acid metabolite of LD01, LD10da, improved T cell activation capability in a malaria vaccine model. Specifically, LD10da demonstrates improved antigen-specific CD8+ T cell expansion when combined prophylactically with an adenovirus-based malaria vaccine. A single dose of LD10da at the time of vaccination is sufficient to increase antigen-specific CD8+ T cell expansion in wild-type mice and in a humanized immune system mouse model. Further, we show that LD10 can be encoded and delivered by a Modified Vaccinia Ankara viral vector and can enhance antigen-specific CD8+ T cell expansion comparable to that of synthetic peptide administration. Therefore, LD10da represents a novel biologic-based immunomodulator that can be genetically encoded and delivered, along with the antigen, by viral or other nucleic acid vectors to improve the efficacy and delivery of vaccines for ineradicable and emerging infectious diseases.